Influence of intravenous 10% amino acids infusion on serum albumin concentration in hypoalbuminemic dogs - Schneider, Sabrina; Hartmann, Katrin; Dörfelt, René (Frontiers in Veterinary Science, 2023)
Objective: To evaluate the effect of parenteral amino acid application in hospitalized hypoalbuminemic dogs. Material and Methods: Medical records of client-owned hypoalbuminemic dogs (albumin ≤25 g/l) were analyzed. Dogs receiving amino acids for only 1 – 2 days, receiving transfusions or surgery, or <6 months of age were excluded. Dogs were grouped as those receiving intravenous amino acids (AA, 80 dogs) over 3 days and longer, and those without additional amino acid treatment (CON, 78 dogs). Duration of hospitalization, albumin and total protein concentrations were compared between groups by Mann-Whitney U test. Course of albumin and total protein concentration was evaluated by Friedman test and Dunn´s multiple comparison test. Significance was set to p ≤0.05. Results: Dogs in group AA received 10% amino acid solution intravenously over median 4 days (3 – 11 days). No significant differences regarding survival and adverse effects were observed between groups. Dogs of group AA had significantly longer duration of hospitalization (median 8 days; 3 – 33 days) compared to group CON dogs (median 6 days, 3 – 24 days; p <0.001). Initial albumin concentration was lower in group AA compared to CON (p <0.001). This difference was no longer present on day 2 (p = 0.134). Conclusions and clinical relevance: Intravenous application of 10% amino acid solution in hypoalbuminemic dogs can improve albumin concentration after 2 days, but does not influence outcome.